2018
DOI: 10.29309/tpmj/18.4570
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Second Molar

Abstract: It is important for a dental practitioner to have a clear understanding of the root canal morphology and its variations to perform successful root canal treatment. The inability to identify and adequately treat all canals of root canal system may contribute to the failure of root canal treatment. Objectives: Clinically determine the frequency or numbers of root canals per tooth in the maxillary second molar teeth in the local population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Whereas the study by Shafqat et al on Pakistani population has reported the prevalence of 50%. 19 The authors did not find any further study on second maxillary molars in Pakistani population. The findings of current study were in line with the results reported in American (56.9%) and Brazilian (58%) populations.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Whereas the study by Shafqat et al on Pakistani population has reported the prevalence of 50%. 19 The authors did not find any further study on second maxillary molars in Pakistani population. The findings of current study were in line with the results reported in American (56.9%) and Brazilian (58%) populations.…”
Section: Discussionmentioning
confidence: 88%
“…18 The prevalence of one and four canals in the current research were comparable with the findings of study conducted by Shafqat et al on the Pakistani population. 19 The prevalence of second maxillary molar teeth with one and two canals was significantly higher in Pakistani population as compared to the Brazilian population (0%).3 Conversely, Pecora and colleagues reported significantly higher percentage of second maxillary molars (42%) with 4 canals in Brazilian cohort. 3 The percentages of four canals in Pakistani population were found to be 25.3% in current study and 21.25% as reported by Shafqat et al 19 Accordingly, Peikoff et al noted 22.7% of the maxillary second molars with four canals in the American population while using radiographic method to assess the number of canals.…”
Section: Discussionmentioning
confidence: 91%
“…Studies on internal and external anatomy of teeth have shown that complex anatomical variation can occur in all teeth. (Shafqat et al, 2018) The factors that play a role in these variations include ethnicity, age, gender and study design (Ratanajirasut et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…False assumptions about the anatomy of the root canal of teeth can lead to misdiagnosis, inadequate debridement, step formation and instrument breakage during root canal care(Shafqat, Munir and Sajid, 2018). Problems encountered during endodontic treatment of permanent molar teeth indicate the need for increased knowledge of root canal system anatomy(Kanyal et al, 2016).…”
mentioning
confidence: 99%